2008
DOI: 10.1007/s10562-008-9678-z
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Desilicated ZSM-5, ZSM-12, MCM-22 and ZSM-12/MCM-41 Derivatives in Isomerization of α-Pinene

Abstract: Limited information is available on the isomerization of a-pinene proceeding on zeolites and related desilicated materials. We wish therefore to report on the title reaction proceeding over ZSM-5, ZSM-12 and MCM-22 type zeolites, parent and modified by the sodium hydroxide treatment. The NaOH solutions of various concentrations (0.05-1 M) were used as a desilicating agent. Such treatments with basic solutions were applied: (i) under atmospheric pressure, and (ii) under hydrothermal conditions. It was shown tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(40 citation statements)
references
References 35 publications
3
36
0
Order By: Relevance
“…It has been reported that the RC of zeolite can be effectively improved with the mild alkali-treatment conditions [38] and then decreases with harsh treatment conditions [46,47]. We also observe a similar phenomenon.…”
Section: Effects Of the Alkali Treatment On Different Pore Systems Ofsupporting
confidence: 84%
“…It has been reported that the RC of zeolite can be effectively improved with the mild alkali-treatment conditions [38] and then decreases with harsh treatment conditions [46,47]. We also observe a similar phenomenon.…”
Section: Effects Of the Alkali Treatment On Different Pore Systems Ofsupporting
confidence: 84%
“…90,91 This method can be used to introduce intracrystalline mesopores with high degree of interconnectivity in zeolite crystals of different framework types. 36,[92][93][94][95][96] In contrast to dealumination, desilication does not significantly affect the acidity and the crystalline structure of zeolites. 97 As also depicted schematically in Fig.…”
Section: Demetalationmentioning
confidence: 99%
“…[6][7][8][9][10][11][12] Nowadays, an impressive variety of approaches forms a nanoscale toolbox that can be used to design high-performance zeolite catalysts by optimizing porosity, as well as other key parameters as, for example, acidity and composition. [12][13][14][15][16][17] The selective extraction of silicon from the zeolite framework in alkaline medium (typically NaOH) has proven to be an effective, versatile, and simple post-synthesis treatment to introduce mesoporosity in a broad variety of zeolite structures such as MFI, [18] MTW, [19] MOR, [20] BEA, [21] AST, [22] FER, [23] MWW, [24] IFR, [25] and STF. [26] Nevertheless, a major drawback of desilication remained that its applicability is limited by the silicon/aluminum ratio in the framework.…”
Section: Introductionmentioning
confidence: 99%